prove

Asked by  | 5th Oct, 2008, 08:47: PM

Expert Answer:

average velocity =( vo + v) / 2

distance travelled  is(  x =  v ' t, where v'  = (vo + v ) /2 

subsituting the value in above equation

you will get x =  (vo   +  vo  + at ) t / 2

and finally x =  vo t +  at2 / 2 , in this equation replace x with h,  vo with u and as the body is moving under gravity (opposite to gravity repace a with (- g ))  solve the equation and get the answer,

Vo is the initial velocity x is the distance covered , h is the height

Answered by  | 5th Oct, 2008, 11:23: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.